A Qualitative Analysis of Teachers’ Perception of Classroom Pedagogical Accompaniment Program - Arrellano, Rodrigo; García, Leidy Y.; Philominraj, Andrew; Ranjan, Ranjeeva (Frontiers in Education, 2022)
The need to increase educational quality has led public policymakers to create and implement strategies for improving teachers’ skills. One such strategy, adapted in Chile, is the classroom accompaniment program, which has become a case of teacher professional development. The present study primarily seeks to understand public schoolteachers’ perception on classroom pedagogical accompaniment program (CPAP), and at the same time its effectiveness. This qualitative research is a case study framed within an interpretive paradigm, in which semi-structured interviews were conducted to collect data. A content analysis was done with 4 categories and 10 subcategories of perceptions attributed to the program and its effectiveness by 13 teachers, 8 females and 5 males, belonging to four public educational establishments. The results show opposed perceptions about the existing accompaniment program. On one hand, some teachers rate it positively and consider it beneficial for them and their students, who also received adequate feedback. On the other hand, another group of teachers considered that there were no positive contributions to their work performance, with impacts including greater reticence during the in-class observation process. Thus, the study concludes that the initial orientations and instruction regarding the role of the observing teacher are fundamental for the classroom accompaniment process to be effective and that it can be a valuable tool to apply for improving teacher performance.